2020
DOI: 10.1002/vnl.21782
|View full text |Cite
|
Sign up to set email alerts
|

Pani‐Ag/PVA nanocomposite: Gamma induced changes in the thermal and optical characteristics

Abstract: The gamma (γ) induced modifications in the synthesized Pani-Ag/PVA nanocomposite (NCP) thermal and optical characteristics have been depicted. The induced effect was investigated applying X-ray diffraction, differential scanning calorimetry, and UV-spectroscopy. Further, the color intensity (ΔE) of the irradiated NCP and blank has been estimated. The γ radiation decreases the optical band gap value from 2.65 to 1.54 eV owing to the randomly amorphous dominance in the irradiated NCP. Moreover, γ radiation induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[ 1 ] Moreover, Heiba et al showed that the optical and dielectric properties of PVA/CMC blend could be improved by chalcogenide nano fillers. [ 10 ] Furthermore, the effect of the gamma irradiation on the optical and thermal properties of Pani‐Ag/PVA nanocomposites (NCs) was examined in Reference [39].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Moreover, Heiba et al showed that the optical and dielectric properties of PVA/CMC blend could be improved by chalcogenide nano fillers. [ 10 ] Furthermore, the effect of the gamma irradiation on the optical and thermal properties of Pani‐Ag/PVA nanocomposites (NCs) was examined in Reference [39].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the cage effect that includes the free radical re-combination prior to taking part in reactions that encourage crosslinking [32,33]. Through crosslinking, the chains can be joined end to end; the increase of the polymeric chain length add also to the shift of Tm toward higher temperatures [23]. Fig.…”
Section: Differential Thermal Analysis (Dta)mentioning
confidence: 75%
“…This wide peak is due to the amorphous PANI as the amorphous PANI has two wide peaks at 2 = 20.4° and 24.8°. These peaks are owing to the periodicity parallel and perpendicular to PANI chains, correspondingly [23]. No peaks appeared for Co indicating the incorporation of Co in the NCP matrix.…”
Section: Ray Diffractionmentioning
confidence: 99%
“…Also, the presence of more negative charges creates novel interior bonds in the NC. Besides, the minute size of the Pd NPs decreases the atomic volume occupied by Pd and thus increases its density, leading to the enhancement of the absorbance [46,47].…”
Section: Absorption Coefficient Investigationmentioning
confidence: 99%